Analysis of the application of the product-service system in the development of MSMEs on the teras jajan - Mardhiyah, Wendy Febrianty; Azzahra, Paramitha Widyadhari; Alamsyah, Nanang (Institute of Computer Science (IOCS), 2025)
In this digital era, people must adapt to the developments that occur, one of which is business competition. Business competition results in companies having to keep innovating in order to win the competition and continue to maintain market share and customers. This transformation gave birth to the conception of the Product-Service System (PSS), a paradigm that integrates tangible and intangible aspects in the value proposition to consumers. PSS or Product Service System is a reliable solution in business competition in this digital era to answer questions about how to develop a business that requires balance and strength to keep this business running for a long duration. The research methods used are Descriptive Qualitative, Interview, and Observation where these three studies aim to understand the phenomena that occur. Based on the results of the research conducted, it is found that of the nine quadrants of the Product-Service System (PSS), only four quadrants are feasible to be applied to Teras Jajan MSMEs, namely Product Related Service, Product Pooling, Outsourcing, and Functional Result. This has relevance to the problems faced by Teras Jajan MSMEs, namely the owners to develop the business they are running